Discriminative and descriptive sensory analysis of guacamole dressing made from “Hass” avocado powder (2020)
ABSTRACT: The guacamole is a product based on avocado very desirable in world gastronomy. The aim of this study was to select a formulation of guacamole prepared with avocado powder and fresh avocado (GAP+FA) from sensory methodologies. Initially, a discriminative ranking analysis was performed, which allowed to select the best overall quality formulation and subsequently a descriptive analysis was performed by a multidimensional approach to the selected GPA+AF and commercial guacamole obtained with fresh avoca-do (GAF), where descriptors of appearance, color, flavor and texture were evaluated. Trained panelists were used, who evaluated 15 formulations obtained from the variables: dry solids of guacamole (DSGuacamole) (30,30–25,25–20,20%), dry solids provided by AF (DSAF) (0-25-50%) and lime color (0–0,015–0,030%). The discriminative methodology selected two formulations: 1) DSGuacamole = 25,25%, DSFA = 25% and lime color = 0,015% (F2) and 2) DSGuacamole = 30,30%, DSFA = 50% and lime color = 0,030% (F16). According to the greater similarity with the GFA sample, regarding the contribution of DSGuacamole and higher content of dry solids provided by the AP (DSAP), F2 formula was selected for the descriptive test, which provided descriptors with desirable characteristics by consumers of Tex-Mex products.